2016
DOI: 10.1016/j.actatropica.2016.06.028
|View full text |Cite
|
Sign up to set email alerts
|

AFAP-1L1-mediated actin filaments crosslinks hinder Trypanosoma cruzi cell invasion and intracellular multiplication

Abstract: Host actin cytoskeleton polymerization has been shown to play an important role during Trypanosoma cruzi internalization into mammalian cell. The structure and dynamics of the actin cytoskeleton in cells are regulated by a vast number of actin-binding proteins. Here we aimed to verify the impact of AFAP-1L1, during invasion and multiplication of T. cruzi. Knocking-down AFAP-1L1 increased parasite cell invasion and intracellular multiplication. Thus, we have shown that the integrity of the machinery formed by A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…The importance of actin cytoskeleton during parasite replication has been previously demonstrated by other authors (24)(25)(26). AFAP-1L1 knockout cells, which showed lower actin polymerization, were found to have higher intracellular replication rate of strain T. cruzi (26).…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…The importance of actin cytoskeleton during parasite replication has been previously demonstrated by other authors (24)(25)(26). AFAP-1L1 knockout cells, which showed lower actin polymerization, were found to have higher intracellular replication rate of strain T. cruzi (26).…”
Section: Resultssupporting
confidence: 52%
“…The importance of actin cytoskeleton during parasite replication has been previously demonstrated by other authors (24)(25)(26). AFAP-1L1 knockout cells, which showed lower actin polymerization, were found to have higher intracellular replication rate of strain T. cruzi (26). Previous studies have reported that a more rigid cytoskeleton retains the parasite within the host cell (24), while its disarrangement would be more conducive to the free intracellular replication of T. cruzi (25).…”
Section: Resultsmentioning
confidence: 61%
“…After shRNA transduction cells were analyzed by flow cytometry to check the knocking down expression of Gal-3. Transduction and expression analysis were performed as described by Araújo et al ( 2016 ) WT, control knockdown (CTRL KD) and Gal-3 KD cells were used.…”
Section: Methodsmentioning
confidence: 99%
“…Cell culture and parasite maintenance -Immortalised macrophages (macrophages C57) were derived from the bone marrow of C57BL/6 mice and maintained according to Araujo et al (37) L. (L.) amazonensis promastigotes (IFLA/BR/67/PH8) were maintained in Brain Heart Infusion -HiMedia medium supplemented with 10% foetal bovine serum (FBS) (Cultilab, Campinas, Brazil), 100 mg of gentamicin/mL and 2 mM Lglutamine (GibcoBRL, Life Technologies, New York) at 23ºC. Promastigotes in the stationary phase (metacyclic) were used in the experiments.…”
Section: Crotalus Durissus Collilineatus Serum and Bothropsmentioning
confidence: 99%
“…For both protocols, cells were fixed with Bouin's solution (HT10132 Sigma Aldrich) and stained with Giemsa (1:20 -P3288 Sigma Aldrich). (37) Finally, the coverslips were analysed under a light microscope to assess the following parameters: number of cells with invaded parasites (invasion rate) and total number of parasites invaded to these cells in a total of 200 cells examined randomly. Three independent experiments were performed in triplicate for each treatment.…”
Section: Cellular Viability In Promastigote Forms Of L (L)mentioning
confidence: 99%